PELATIHAN BERWIRAUSAHA MELALUI DIGITAL MARKETING - Nurul Farida; Triani Ratnawuri; Lilian Mega Puri (UM Metro, 2021)
ABSTRAK Kegiatan pengabdian bertujuan untuk melatih kemampuan berwirausaha melalui digital marketing. Kegiatan pengabdian diikuti oleh remaja panti asuhan Tuma’ninah Yasin kota Metro yang menjadi mitra dalam kegiatan pengabdian ini. Metode yang digunakan teknik demonstrasi, tanya jawab, diskusi dan praktik. Hasil pelatihan yang didapat adalah sejumlah 91,71. % peserta memiliki keterampilan memanfaatkan digital marketing untuk berwirausaha dengan menjual produk kerajinan kain flanel. Kata kunci : berwirausaha, digital marketingABSTRACT The purpose of of this dedication is to train entrepreneurial skills through digital marketing. The community service activity was followed by the teenagers of the Metro city Tuma'ninah Yasin orphanage who became partners in this service activity. The methods used were demonstration techniques, question and answer, discussion and practice. The results of the training obtained were 91.71. % of participants have the skills to take advantage of digital marketing for entrepreneurship by selling flannel craft products. Keywords: entrepreneurship, digital marketing